2015
DOI: 10.3233/jnd-150099
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin Converting Enzyme Inhibitor Lisinopril Improves Muscle Histopathology but not Contractile Function in a Mouse Model of Duchenne Muscular Dystrophy

Abstract: Background Angiotensin converting enzyme inhibitors (ACEi) are the current standard of care treatment for cardiac dysfunction in Duchenne muscular dystrophy patients. We previously showed treatment with an ACEi plus mineralocorticoid receptor (MR) antagonist improves limb and respiratory skeletal muscles, in addition to cardiac muscles, in a dystrophic mouse model at 20 weeks-of-age. Objective To determine whether previously observed preclinical benefits of an ACEi plus MR antagonist on dystrophic skeletal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 18 publications
(30 reference statements)
0
33
2
Order By: Relevance
“…Abdominal muscles that help to support respiration, had a 30% lower amount of damage in the LS treated group compared with the untreated het group (t-test P = 0.01). Surprisingly, and in contrast to our previous studies with either LS or lisinopril alone [6, 8], quadriceps showed only a 9% reduction of damage and only in the EL group, but not the LS group. However ongoing damage in this untreated het cohort was less than 10% overall, and fibrosis has not accumulated in quadriceps of het mice at this age (Fig.…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Abdominal muscles that help to support respiration, had a 30% lower amount of damage in the LS treated group compared with the untreated het group (t-test P = 0.01). Surprisingly, and in contrast to our previous studies with either LS or lisinopril alone [6, 8], quadriceps showed only a 9% reduction of damage and only in the EL group, but not the LS group. However ongoing damage in this untreated het cohort was less than 10% overall, and fibrosis has not accumulated in quadriceps of het mice at this age (Fig.…”
Section: Resultscontrasting
confidence: 99%
“…On the day of sacrifice, the body weight of each mouse was recorded and resting, non-anesthetized, non-invasive electrocardiographic recordings were taken using the ECGenie system (Mouse Specifics Inc.) as previously described [8]. Analysis of QT- interval, heart rate, and heart rate variability was done using time intervals when paws were in contact with the electrodes and heart rate (HR) remained consistent.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations